Active hepatitis B virus vaccination in the prevention of viral reactivation in liver transplantation recipients with previous hepatitis B infection: a cohort study - Eric Adler; Yasemin Krucker; Mirjam Kolev; Nasser Semmo (Swiss Medical Weekly)
BACKGROUND AND AIM OF THE STUDY: For many years, the standard treatment following liver transplantation for hepatitis B has been a combination of hepatitis B immunoglobulin and nucleos(t)ide analogues such as entecavir and tenofovir. However, because of the high costs and logistical challenges of long-term hepatitis B immunoglobulin use, alternative approaches such as vaccination and hepatitis B immunoglobulin-free regimens are being explored. This study gathered information on a potential response (or lack thereof) and addressed the adverse events associated with active immunisation in liver transplant recipients in a Swiss cohort with hepatitis B virus (HBV)-related diseases after discontinuing hepatitis B immunoglobulin.